Genesis of Late Miocene-Pliocene lacustrine palygorskite and calcretes from Kırşehir, central Anatolia, Turkey. (June 2014) - Kadİr, S. and Eren, M. and Külah, T. and Önalgİl, N. and Cesur, M. and Gürel, A.
Abstract: This paper addresses the mineralogy, geochemistry, and genesis of palygorskite and associated calcretes in the Kırşehir region. In this area, the Quaternary calcretes are present within and/or on lacustrine mudstones of the Kızılırmak Formation (Late Miocene-Pliocene). The calcretes occur in the form of nodules, tubes, fracture-infills, and hard laminated crusts (hardpans). Calcrete samples are predominantly composed of calcite associated with smectite, quartz, feldspar, and minor palygorskite. The lacustrine mudstone samples consist mainly of smectite and palygorskite with minor calcite, quartz, feldspar, illite, kaolinite and amorphous material. Petrographic studies revealed that the calcrete samples are predominantly micrites that were partially converted to microsparites by recrystallization. Scanning and transmission electron microscopy images indicate that palygorskite fibres formed authigenically on and between calcite rhombs in the calcrete samples and at the edges of smectite flakes of host rocks adjacent to the calcretes. The oxygen and hydrogen stable isotope values of the calcite suggest that it precipitated from meteoric water under arid or seasonally arid climatic conditions. Calcite precipitation occurred in the vadose zone, as evidenced by desiccation cracks and vadose pisolites. The enrichment of Rb+Ba±Sr and Light Rare Earth Elements (LREE) relative to Heavy Rare Earth Elements (HREE)with a distinct negative Eu anomaly are responses to the fractionation of volcanogenic feldspar and hornblende under the influence of meteoric water. The palygorskite associated with calcretes was precipitated from alkaline water rich in Si, Al and Fe and low in Mg. The palygorskite precipitation occurred at increased temperatures, characterising the advanced stage of calcrete formation which lowers the Ca content in the soil water. The required chemical elements for palygorskite and calcite were most likely derived from the dissolution of smectitic clays, ignimbrites and carbonate minerals.